Organizing Challenges Faced by Trade Unions in the Hospitality Industry of Zimbabwe - Farai Ncube; Olabanji Oni (Eurasian Publications, 2023)
Globally there are a lot of developments and changes happening in the tourism industry affecting the traditional business operations and with a serious effect on employment relations patterns. Trade unions have been at the receiving end owing to these changes. New forms of employment coupled with other changes have adversely affected the ability of trade unions to effectively organize. While union strength is measured by a number of aspects, membership remains the main indicator of union power. In this article, we examine the organizing challenges faced by the Trade Unions in the Hospitality Industry of Zimbabwe. We employ a qualitative study utilizing a sample of 80 respondents drawn from union officials (10), shop stewards (40) and management representatives (30). The study reveals that the unions face a myriad of challenges ranging from lack of resources to effectively organize and support all initiatives in place, political persecution affecting member perceptions, lack of management support, destroying all union efforts as well as changing demographics and employment conditions among other challenges. We maintain that the survival of a trade union depends primarily on its ability to organize workers. We advance the argument that the industry is not immune to the developments and changes happening in the contemporary world of work and for unions to survive they have to co-evolve. We conclude that the identified challenges can actually be opportunities for the trade unions